Optymalna lokalizacja obiektów - Gaspars, Helena (Optimal Facilities' Location, 2007)
The paper presents several optimization models concerning the location of a chain of facilities which belong to one proprietor. Therefore, the models' goal consists in maximizing his total profit and not the gain of each facility separately. On one hand, the formulated models are partially based on Lösch's, Isard's and Christaller's theories. On the other hand, the author shows their connection with some operations research's areas.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1167, s. 51-64